In the previous section, we saw the theorem 1 related to symmetric and skew symmetric matrices. In this section, we will see theorem 2.
Theorem 2
Any square matrix can be expressed as the sum of a symmetric matrix and a skew symmetric matrix.
Proof:
Let A be a square matrix. First, we will prove that,
A=12(A+A′) + 12(A−A′)
112(A+A′) + 12(A−A′) 2 = 12A + 12A′ + 12A − 12A′ 3 = 12A + 12A + 12A′ − 12A′ 4 = 12A + 12A 5 = A
•
Now we can write the proof for theorem 2 in steps:
1.
We just proved that, A can be written as the sum of two terms.
12(A+A′) and 12(A−A′)
2. Consider the first term.
•
In this term, we know (from theorem 1) that, (A+A') is a symmetric matrix.
• We need to prove that, 12(A+A′) is also a symmetric matrix.
•
For that, we need to prove:
12(A+A′) = [12(A+A′)]′
•
In other words, we need to prove:
12B = [12B]′
♦ Where B = A + A'
• This can be proved in 4 steps:
(i) B is symmetric.
♦ That means, B = B'
♦ That means, 12B = 12B′
(ii) For any matrix X, we have: kX' = (kX)'
(iii) So the result in (i) becomes:
12B = 12B′ = [12B]′
(iv) By picking the first and last terms in (iii), we get:
12B = [12B]′.
•
This is same as:
12(A+A′) = [12(A+A′)]′
•
So 12(A+A′) is a symmetric matrix.
3. Consider the second term.
•
In this term, we know (from theorem 1) that, (A−A') is a skew symmetric matrix.
•
We need to prove that, 12(A−A′) is also a skew symmetric matrix.
•
For that, we need to prove:
12(A−A′) = −[12(A−A′)]′
•
In other words, we need to prove:
12C = −[12C]′
♦ Where C = A − A'
•
This can be proved in 4 steps:
(i) C is skew symmetric.
♦ That means, C = -C'
♦ That means, 12C = −12C′
(ii) For any matrix X, we have: kX' = (kX)'
(iii) So the result in (i) becomes:
12C = −12C′ = −[12C]′
(iv) By picking the first and last terms in (iii), we get:
12C = −[12C]′.
•
This is same as:
12(A−A′) = −[12(A−A′)]′
•
So 12(A−A′) is a skew symmetric matrix.
4. So the first term is a symmetric matrix. Also, the second term is a skew symmetric matrix.
•
Thus we effectively wrote matrix A as the sum of a symmetric matrix and a skew symmetric matrix.
•
Theorem 2 is proved.
Solved example 19.15
Express the matrix B = [3112−10−4128−913] as the sum of a symmetric matrix and a skew symmetric matrix.
Solution:
1. Write the transpose of B:
B' = [3−10811−4−921213]
2. Let P=12(B+B′) and Q=12(B−B′)
3. Finding P and proving that, it is symmetric:
• If we try to write P', we will get the same P. So P is a symmetric matrix.
4. Finding Q and proving that, it is skew symmetric:
• We see that, Q' = -Q. So it is a skew symmetric matrix.
5. Checking the sum:
The link below gives a few more solved examples:
Exercise 19.3
In the next section, we will see elementary operation of a matrix and invertible matrices.
Copyright©2024 Higher secondary mathematics.blogspot.com
No comments:
Post a Comment